2023
DOI: 10.3390/ijerph20075298
|View full text |Cite
|
Sign up to set email alerts
|

Adaptogens on Depression-Related Outcomes: A Systematic Integrative Review and Rationale of Synergism with Physical Activity

Abstract: Depression is considered the most important disorder affecting mental health. The aim of this systematic integrative review was: (i) to describe the effects of supplementation with adaptogens on variables related to depression in adults; and (ii) to discuss the potential combination with physical exercise to aid planning and commissioning future clinical research. An integrative review was developed complementing the Preferred Reporting Items for Systematic reviews and Meta-Analyses statement (PROSPERO registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…The formulation (500-1000 μg/mL) was also tested for unravelling its effects on isolated mouse hypothalamus, in order to assess the activity of neurotransmitters and peptides involved in fatigue and response to stress. [4,22,24] In particular, our attention focused on dopamine, serotonin, NPY, and orexin-A that are known to interact in the hypothalamic nuclei for regulating different neuroendocrine functions, among which also feeding, sleeping, anxiety, and response to stress. In this context, the formulation effect on the turnover of dopamine and serotonin was investigated, through the assessment of their turnover that is generally expressed as ratio between parent neurotransmitter molecules and main metabolites.…”
Section: Neuromodulatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formulation (500-1000 μg/mL) was also tested for unravelling its effects on isolated mouse hypothalamus, in order to assess the activity of neurotransmitters and peptides involved in fatigue and response to stress. [4,22,24] In particular, our attention focused on dopamine, serotonin, NPY, and orexin-A that are known to interact in the hypothalamic nuclei for regulating different neuroendocrine functions, among which also feeding, sleeping, anxiety, and response to stress. In this context, the formulation effect on the turnover of dopamine and serotonin was investigated, through the assessment of their turnover that is generally expressed as ratio between parent neurotransmitter molecules and main metabolites.…”
Section: Neuromodulatory Effectsmentioning
confidence: 99%
“…[20,21] Therefore, the present study evaluted the modulatory effects of a commercial formulation including water extracts from R. rosea, M. oleifera, and U. pinnatifida on hypothalamic factors involved in fatigue and response to the stress, among which CRH, NPY, orexin A, and serotonin. [4,[22][23][24][25] The activity of the formulation was also evaluated in terms of intrinsic antioxidant properties, alongside with content of specialised metabolites, namely phenolic and flavonoid compounds. These compounds are known to exert protective and neuromodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of numerous in vitro and in vivo studies has shown that it possesses properties such as anticancer, anti-stress, immunomodulatory, hypoglycemic, hypolipidemic, cardioprotective, antibacterial, and anticancer effects. [5,7,8,9].…”
Section: Uses Of Ashwagandhamentioning
confidence: 99%